2018
DOI: 10.1016/j.gaitpost.2017.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Nervous system excitability and joint stiffness following short-term dynamic ankle immobilization

Abstract: Joint immobilization has been demonstrated to modify neural excitability in subsets of healthy populations, leading to disinhibition of cortical and reflexive pathways. However, these findings may have limited clinical application as most models have investigated casting and rigid immobilization, while many musculoskeletal injuries often utilize dynamic immobilization devices such as boot immobilizers and pneumatic splints that allow for modified ambulation. We therefore aimed to determine the short-term effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…By maintaining in-phase cyclic muscle activation, we have established these neuro-motor pathways remain active regardless of immobilization and weightbearing status while using an HFSC, which is consistent with previous studies. 33 The neuroplasticity while using an HFSC is further demonstrated by the GM demonstrating no significant change in EMG activity. The GM is a primary extensor of the hip while maintaining a balanced pelvis.…”
Section: Discussionmentioning
confidence: 98%
“…By maintaining in-phase cyclic muscle activation, we have established these neuro-motor pathways remain active regardless of immobilization and weightbearing status while using an HFSC, which is consistent with previous studies. 33 The neuroplasticity while using an HFSC is further demonstrated by the GM demonstrating no significant change in EMG activity. The GM is a primary extensor of the hip while maintaining a balanced pelvis.…”
Section: Discussionmentioning
confidence: 98%
“… 46 , 47 The use of external ankle support (e.g., taping, immobilization) has limited evidence for its effectiveness in reducing AMI in patients with CAI; however, its potential to minimize pain during stance may represent an important factor in patients with ALAS. 48 While the extended use of such implements has been hypothesized to negatively affect long-term neuromuscular function and, therefore, postural control, our results demonstrate that neurological adaptations are more critical for patient function than postural control at this stage of injury. Addressing these factors in the early stages of injury has been proposed as a key factor for determining whether patients will go on to develop CAI or if they will “cope” and return to full function after their injury.…”
Section: Discussionmentioning
confidence: 57%
“…Roberts et al 16) examined the effects of 10-day lower limb cast immobilization on corticospinal excitability in young participants and found that it increased up to 24 hours after cast removal. On the other hand, Stirling et al 12) investigated the 30minutes gait effects of ankle immobilization devices on cortical excitability, spinal reflexive excitability, and ankle stiffness, and found no significant changes in these variables. These findings suggest that changes in neural excitability by joint immobilization are the result of long-term nervous system plasticity, at least longer than 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…This study employed a pre-test post-test design to examine the effects of AFO immobilization on corticospinal excitability and ankle joint excursions with an immobilization time of three hours based on previous studies 9,12) .…”
Section: Participants and Methodsmentioning
confidence: 99%